Analysis of The Effect of Supervision, Job Relations, and Compensation on Job Satisfaction and its Impact on Job Performance of CV. Aliansyah Winong Pati - Mohammad Hidayat Mukrom; Agatha Ferijani (Soegijapranata Catholic University, 2019)
This study aims to determine the conditions of job satisfaction, job performance, supervision,job relations, and compensation at CV. Aliansyah; explain the influence of supervision, job relations, and compensation for job satisfaction; the influence of supervision, job relations, and compensation on job performance; the effect of job satisfaction on job performance. The type of research used is explanatory research with a quantitative approach. The variables of this study are supervision,jobrelations, and compensation as independent variables, job satisfaction as a mediator variable and job performance as a dependent variable. The sample in this study were 78 employees working at CV. Aliansyah Winong Pati. The data sources used are primary data and secondary data. The primary data used in this study came from questionnaires by respondents. Secondary data obtained from company data, journals, and previous research. Data analysis methods used are descriptive analysis, regression and path analysis. The results of path analysis show that supervision,job relations, compensation have no significant effect on job satisfaction; supervision, job relations, compensation have a significant effect on performance; Job satisfaction has no significant effect on job performance. Job satisfaction is not a mediating variable because the direct influence of all independent variables (supervision, job relations, compensation) on the dependent variable (job performance) is greater than the indirect effect through job satisfaction.